Kategoria czułości w Olgi Tokarczuk Prowadź swój pług przez kości umarłych. Konceptualizacje metaforyczne - Rycielska, Beata (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The article describes the category of tenderness introduced to fiction and literary theory in the works of Olga Tokarczuk. From the perspective of cognitive linguistics, it is regarded as a schematic concept which, in the conceptualization of a scene, is marked by positive expressions. At the same time, it is one of the cognitive domains constituting the conceptual content of positive emotions and feelings experienced towards the world, here, in particular, towards animals. The article discusses some possible types of conceptual metaphors and gives examples of their manifestations. Moreover, imaginative schemes are distinguished that are the basis of conceptualization of selected categories of the world presented in the work.